1989
DOI: 10.1093/schbul/15.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Social Class, Marriage, and Fertility in Schizophrenia

Abstract: The hypothesis is presented that the etiology of schizophrenia is neurodevelopmental: schizophrenia is a disorder occurring in extremely late maturers, whereas manic-depressive psychosis affects early maturers. This hypothesis is related to recent neurobiological findings and also to the following epidemiological and demographic topics covered by the author in her review of social class, marriage, and fertility in schizophrenia: Kretschmer's observations of body type differences between patients with schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 112 publications
1
46
0
Order By: Relevance
“…Because the behavioral effects of amphetamine in general and amphetamine-induced LI disruption in particular are wellestablished models of psychosis, fortified by the capacity of amphetamine to induce and exacerbate psychosis in healthy and schizophrenic humans as well as enhance striatal DA release in schizophrenia patients (Laruelle et al, 1996(Laruelle et al, , 1999, reduced efficacy of APDs in blocking amphetamine-induced behavioral abnormality allows a strong conclusion that loss of estrogen reduces specifically the antipsychotic potency of APDs. This reduced anti-amphetamine efficacy of APDs on the background of low hormonal level provides a close parallel to reduced efficacy of APD treatment in women with schizophrenia during periods associated with low levels of hormones (Kulkarni et al, 1996;Saugstad, 1989;Seeman, 1989;Seeman and Lang, 1990).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the behavioral effects of amphetamine in general and amphetamine-induced LI disruption in particular are wellestablished models of psychosis, fortified by the capacity of amphetamine to induce and exacerbate psychosis in healthy and schizophrenic humans as well as enhance striatal DA release in schizophrenia patients (Laruelle et al, 1996(Laruelle et al, , 1999, reduced efficacy of APDs in blocking amphetamine-induced behavioral abnormality allows a strong conclusion that loss of estrogen reduces specifically the antipsychotic potency of APDs. This reduced anti-amphetamine efficacy of APDs on the background of low hormonal level provides a close parallel to reduced efficacy of APD treatment in women with schizophrenia during periods associated with low levels of hormones (Kulkarni et al, 1996;Saugstad, 1989;Seeman, 1989;Seeman and Lang, 1990).…”
Section: Discussionmentioning
confidence: 96%
“…Women have a more favorable illness course during the reproductive years, characterized by later onset of symptoms, lower symptom severity, and better response to antipsychotic drug (APD) treatment (Agius et al, 2009;Angermeyer and Kuhn, 1988;Hafner, 2003;Hafner et al, 1989;Iacono and Beiser, 1992;Lindamer et al, 1997;Mortimer, 2007;Pregelj, 2009;Riecher-Rossler and Hafner, 2000;Salem and Kring, 1998;Seeman, 1982Seeman, , 1986Szymanski et al, 1995;Tamminga, 1997). In contrast, menopause is associated with increased vulnerability to illness, elevated symptom severity, and reduced response to treatment (Horacek et al, 2006;Kulkarni et al, 1996Kulkarni et al, , 2008bLane et al, 1999;Salokangas, 1995;Saugstad, 1989;Seeman and Lang, 1990). Increased symptom severity and reduced treatment response are associated also with low-estrogen phases of the menstrual cycle (Ereshefsky et al, 1991;Farina et al, 1981;Lane et al, 1999;Salokangas, 1995;Seeman, 1989;Simpson et al, 1990;Tamminga, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The more favorable course of illness is restricted however to the reproductive years. Postmenopausally, there is elevation in the severity of symptoms and reduced response to treatment, as well as an additional onset peak in women after the age of 40-45 (Horacek et al 2006;Kulkarni et al 1996;Kulkarni et al 2008;Lane et al 1999;Salokangas 1995;Saugstad 1989;Seeman and Lang 1990). Likewise, during reproductive years, intensity of psychosis in schizophrenic women fluctuates along the menstrual cycle so that women are most vulnerable to exacerbation and relapse during low estrogen phases of the cycle (Gattaz et al 1994;Hallonquist et al 1993;Opjordsmoen 1991;Riecher-Rossler et al 1994;Seeman 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Social service workers are interested in the economic status of patients in the center, so the economic support is provided to patients who are in low economic situation [4]. As a result, it was shown that, the burden of caregivers' was decreased and positive developments in their lives were seen [5] [6].…”
Section: Introductionmentioning
confidence: 99%